ANALISIS LAMA WAKTU PELAYANAN LABORATORIUM DI RUMAH SAKIT UMUM DAERAH PASAMAN BARAT - Betti Rosita; Ulfa Khairani (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Hospital laboratory services is one of the activities in hospitals that support quality health services. One indicator of the success of health services in the field of clinical pathology laboratory services is the waiting time for laboratory services. The standard set for laboratory service outcome waiting time is ≤ 140 minutes for blood chemistry and routine blood. This research analyzed the service time of outpatient laboratory that conducted hematology and clinical chemistry examination in the laboratory of Pasaman Barat Hospital. This research is a type of descriptive analytic research that is quantitative and supported by qualitative using cross sectional approach. The result of the research showed that laboratory service time at RSUD Pasaman Barat fulfilled the standard (≤ 140 minutes) for hematology examination 33.94 minutes, clinical chemistry 83.92 minutes, hematology and clinical chemistry 98 minutes. Based on the results of this study, the stages that contribute to the length of time laboratory services for hematological examination lies in the pre analytical stage, for clinical chemistry examination is located at the analytical stage, as well as for hematology and clinical chemistry examination lies in the analytic stage as well as the factors that affect the length of time laboratory services are human resources that is in the ability of officers and infrastructure facilities